2015
DOI: 10.1039/c5fo00094g
|View full text |Cite
|
Sign up to set email alerts
|

Platycodin D isolated from the aerial parts of Platycodon grandiflorum protects alcohol-induced liver injury in mice

Abstract: Platycodin D (PD) is the main active saponin of Platycodon grandiflorum (PG) and is reported to exhibit multiple biological effects, including anti-tumor, anti-inflammation, and anti-obesity properties. Although recently there have been many research reports on the chemical constituents of the plant's roots, only few works have been reported on the aerial parts of PG. In the present study, we report the first isolation of PD from the aerial parts of PG and its protective effect against acute alcohol-induced li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…Platycodin D supplementation promoted activities of antioxidant enzymes, including CAT, SOD, and GSH‐Px (Liu et al, ). Another work also observed that platycodin D treatment reversed the elevated levels of ALT, AST, thereby corroborating results observed in the paper of Li et al (; Wu et al, ).…”
Section: Natural Compounds Beneficial For Ald Treatmentsupporting
confidence: 83%
See 2 more Smart Citations
“…Platycodin D supplementation promoted activities of antioxidant enzymes, including CAT, SOD, and GSH‐Px (Liu et al, ). Another work also observed that platycodin D treatment reversed the elevated levels of ALT, AST, thereby corroborating results observed in the paper of Li et al (; Wu et al, ).…”
Section: Natural Compounds Beneficial For Ald Treatmentsupporting
confidence: 83%
“…The work by Wu et al () uncovered the anti‐inflammatory activity of platycodin D on alcohol‐induced fatty livers. They also found that platycodin D treatment reversed the elevated levels of inflammatory cytokines, including TNF‐α and IL‐6 induced by alcohol (Li et al, , Wu et al, ). In addition, they observed that platycodin D apparently inhibited ethanol‐induced elevation of plasma endotoxin, hinting at its potential protective role against endotoxemia induced by ethanol.…”
Section: Natural Compounds Beneficial For Ald Treatmentmentioning
confidence: 96%
See 1 more Smart Citation
“…The inflammatory cascade and oxidative stress play major roles in alcohol‐induced hepatotoxicity . The antioxidant defense systems essentially include SOD, CAT, and GSH‐related enzymes, which were reported to decrease on ethanol administration . Accordingly, a significant decrease in the levels of SOD, CAT, GSH, and GPx activities was observed in the liver of the ethanol‐administered group of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Platycodin D (PD, Fig. 1), the major active constituent of P. grandiflorum, has received more and more attention due to its pharmaceutical effects, including anti-inflammation (Chung et al, 2008;Zhang et al, 2015), anti-obesity (Zhao et al, 2006), anti-atherosclerosis (Wu et al, 2012), hepatoprotective Li et al, 2015a), and anti-tumor (Luan et al, 2014;Zhao et al, 2015) effects. It is worth mentioning that PD exerts remarkable anti-cancer effects on different kinds of cancer cell lines, including HepG2, MDA-MB-231, U937, K562, PC3, and MCF-7, with main molecular mechanisms such as promoting apoptosis and inhibiting migration and invasion (Tang et al, 2014;Li et al, 2014;Yu and Kim, 2010;Shin et al, 2009;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%